Is There a Role for Oral Antibiotic Preparation Alone Before Colorectal Surgery? ACS-NSQIP Analysis by Coarsened Exact Matching. Issue 7 (July 2017) - Garfinkle, Richard; Abou-Khalil, Jad; Morin, Nancy; Ghitulescu, Gabriela; Vasilevsky, Carol-Ann; Gordon, Philip; Demian, Marie; Boutros, Marylise
Abstract : BACKGROUND: Recent studies demonstrated reduced postoperative complications using combined mechanical bowel and oral antibiotic preparation before elective colorectal surgery. OBJECTIVE: The aim of this study was to assess the impact of these 2 interventions on surgical site infections, anastomotic leak, ileus, major morbidity, and 30-day mortality in a large cohort of elective colectomies. DESIGN: This is a retrospective comparison of 30-day outcomes using the American College of Surgeons National Surgical Quality Improvement Program colectomy-targeted database with coarsened exact matching. SETTINGS: Interventions were performed in hospitals participating in the national surgical database. PATIENTS: Adult patients who underwent elective colectomy from 2012 to 2014 were included. INTERVENTIONS: Preoperative bowel preparations were evaluated. MAIN OUTCOME MEASURES: The primary outcomes measured were surgical site infections, anastomotic leak, postoperative ileus, major morbidity, and 30-day mortality. RESULTS: A total of 40, 446 patients were analyzed: 13, 219 (32.7%), 13, 935 (34.5%), and 1572 (3.9%) in the no-preparation, mechanical bowel preparation alone, and oral antibiotic preparation alone groups, and 11, 720 (29.0%) in the combined preparation group. After matching, 9800, 1461, and 8819 patients remained in the mechanical preparation, oral antibiotic preparation, and combined preparation groups for comparison with patients without preparation. On conditional logistic regression of matched patients, oral antibiotic preparation alone was protective of surgical site infection (OR, 0.63; 95% CI, 0.45–0.87), anastomotic leak (OR, 0.60; 95% CI, 0.34–0.97), ileus (OR, 0.79; 95% CI, 0.59–0.98), and major morbidity (OR, 0.73; 95% CI, 0.55–0.96), but not mortality (OR, 0.32; 95% CI, 0.08–1.18), whereas a regimen of combined oral antibiotics and mechanical bowel preparation was protective for all 5 major outcomes. When directly compared with oral antibiotic preparation alone, the combined regimen was not associated with any difference in any of the 5 postoperative outcomes. LIMITATIONS: This study was limited by its retrospective design with heterogeneous data. CONCLUSIONS: Oral antibiotic preparation alone significantly reduced surgical site infection, anastomotic leak, postoperative ileus, and major morbidity after elective colorectal surgery. A combined regimen of oral antibiotics and mechanical bowel preparation offered no superiority when compared with oral antibiotics alone for these outcomes. SeeVideo Abstract athttp://links.lww.com/DCR/A358 .